A study on the relationship between technological affordance of age-appropriate smart wearable devices and the well-being of older adults - Zhang, Hao; Yang, Shusheng; Lin, Yili (Frontiers in Public Health, 2025)
IntroductionGlobal population aging is intensifying, posing significant challenges to care for older adults. In this context, age-appropriate smart wearable devices, with their capabilities for efficient physiological monitoring, disease prevention, and safety protection, play an important role in supporting the health and independence of older adults. However, the relationship between the technological affordance of these devices and the well-being of older adults has not been fully explored. In this study, an integrated theoretical model was constructed based on Technological Affordance Theory (TAT), Self-Determination Theory (SDT), Stimulus-Organism-Response (SOR) theory, and Socioemotional Selectivity Theory (SST).MethodsData from 233 older adults using age-appropriate smart wearable devices were collected through a questionnaire, and structural equation modeling (SEM) was used to analyze the data.ResultsThe results indicate that the visibility (β = 0.155–0.238, p < 0.05), interactivity (β = 0.155–0.304, p < 0.05), and directiveness (β = 0.292–0.395, p < 0.001) of age-appropriate smart wearable devices are significantly and positively correlated with older adults’ sense of autonomy, competence, and relatedness. Furthermore, these psychological needs are significantly and positively correlated with their overall well-being (β = 0.184–0.352, p < 0.01). Sense of autonomy, competence, and relatedness significantly mediated the relationship between technological affordance and older adults’ well-being (indirect effects = 0.034–0.139, 95% confidence interval [CI] excluding 0).DiscussionThis study reveals that technological affordance is indirectly positively correlated with the well-being of older adults via their psychological needs, offering practical insights for the design and development of age-appropriate smart wearable devices.